Functional hip joint centre determination in children with cerebral palsy - Öztürk, Orhan; Salami, Firooz; Musagara, Arik Rehani; Demirbüken, İlkşan; Polat, M. Gülden; Wolf, Sebastian Immanuel; Götze, Marco (Gait & posture, 2021)
Background - Although functional methods determining the hip joint center (HJC) are becoming increasingly popular, no systematic investigation has been conducted yet to assess the reliability of functional hip joint calibration in patients with cerebral palsy (CP). - Research question - What is the most reliable way to conduct functional calibration motions for estimating HJC location in children with CP and movement disorders? - Methods - Twenty-two patients with CP were included in the study. A marker set for Plug-in Gait with additional cluster markers was used. Two functional calibration movements, including a new movement, were proposed and tested with one and three repetitions each. Functional HJCs were determined using the SCoRE approach and compared to results obtained by applying the conventional regression method for assessing face validity. - Results - The choice of calibration movement had significant impact on SCoRE residuals and HJC location. Increasingly repeating calibration movements did not improve results. A modified star movement by allowing the toes to tip the ground provided the most reliable data and is feasible for children with GMFCS level I-III. The feasibility of the method is further improved by analyzing hip motion in the contralateral stance limb and, among the calibration movements, gave the most precise HJC estimation. - Significance - Type and performance of the functional calibration movement is one key factor for determining a robust HJC. Analyzing the data in the stance leg via the modified star motion yielded robust and reasonable results for the HJC location, which should be validated in further studies that include imaging methods. Using one repetition instead of three seems promising in terms of feasibility for patients with movement disorder.
Gesehen am 17.11.2021